Intelligent sowing depth regulation system based on Flex sensor and Mamdani fuzzy model for a no-till planter - Li, Mingwei; Xia, Xiaomeng; Zhu, Longtu; Zhou, Renyi; Huang, Dongyan (International Journal of Agricultural and Biological Engineering, 2021)
Sowing depth has an important impact on the performance of no-tillage planters, it is one of the key factors to ensure rapid germination. However, the consistency of sowing depth is easily affected by the complex environment of no-tillage operation. In order to improve the performance of no-tillage planters and improve the control precision of sowing depth, an intelligent depth regulation system was designed. Three Flex sensors installed on the inner surface of the gauge wheel at 120° intervals were used to monitor the downward force exerted by the seeding row unit against ground. The peak value of the output voltage of the sensor increased linearly with the increase of the downward force. In addition, the pneumatic spring was used as a downforce generator, and its intelligent regulation model was established by the Mamdani fuzzy algorithm, which can realize the control of the downward force exerted by the seeding row unit against ground and ensure the proper seeding depth. The working process was simulated based on MATLAB-Simulink, and the results showed that the Mamdani fuzzy model performed well in changing the pressure against ground. Field results showed that when the operating speed was 6 km/h, 8 km/h and 10 km/h, the error of the system's control of sowing depth was ±9 mm, ±12 mm, and ±22 mm, respectively, and its sowing performance was significantly higher than that of the unadjusted passive operation.Keywords: Flex sensor, Mamdani fuzzy model, sowing depth, intelligent regulation system, no-till planterDOI: 10.25165/j.ijabe.20211406.5939Citation: Li M W, Xia X M, Zhu L T, Zhou R Y, Huang D Y. Intelligent sowing depth regulation system based on Flex sensor and Mamdani fuzzy model for a no-till planter. Int J Agric & Biol Eng, 2021; 14(6): 145–152.